Participation of university actors in the territory (Educational Knowledge, 2020)
The University, created by and for the service of society, must be a driving force for the country's development. In this sense, this article analyzes the participation of university stakeholders in the local community, based on the experience of the Territorial Polytechnic University in Venezuela.It is the product of research using mixed methods: documentary and field data, including a questionnaire administered to a purposive sample of 103 engineering graduates and interviews with nine informants: three university faculty/administrators, three business owners, and three local residents. The quantitative data revealed that 60.7% of graduates have adequate working conditions; 49.7% carry out socioeconomic intervention activities in their communities; and only 46.4% believe there is a strong university-community connection.The qualitative data corroborate the weak participation of university graduates in their communities, as well as the fragile link between the university, the productive sector, and the community. This calls for a university that undertakes actions aimed at training well-rounded professionals who contribute to territorial development.
Keywords: Participation; university; territory; productive sector